Advancing Women's Leadership in United Arab Emirates Higher Education: Perspectives from Emirati Women - Shaikha Ali Al-Naqbi; Semiyu Adejare Aderibigbe (MDPI AG, 2024)
The imperative for an ongoing review and comprehension of the challenges and methodologies for enhancing diversity and inclusion of women in senior leadership within higher education is well-documented. This study aims to illuminate the perspectives of Emirati women regarding their leadership trajectories, evaluating the effectiveness of current policies, the obstacles encountered, and strategies to advance women's leadership in higher education. Utilizing a concurrent mixed-methods approach, we collected and analyzed both quantitative and qualitative data from 103 female Emirati leaders in higher education institutions across the United Arab Emirates (UAE). The findings reveal a prevailing sentiment among participants that policies intended to promote Emirati women's inclusion in senior leadership roles are mostly ineffective. Key challenges identified include barriers to career progression, disparities in institutional support, and pervasive gender biases. However, participants also offered insights into potential strategies to enhance the inclusion of Emirati women in leadership positions, including leadership training programs, robust policy development, and initiatives to improve work-life balance, networking opportunities, and reward systems.